On the high temperature coarsening kinetics of γ′ precipitates in a high strength Co37.6Ni35.4Al9.9Mo4.9Cr5.9Ta2.8Ti3.5 fcc-based high entropy alloy. (15th September 2019) - Pandey, Prafull; Kashyap, Sanjay; Palanisamy, Dhanalakshmi; Sharma, Amit; Chattopadhyay, Kamanio
Abstract: The paper reports evolution of two-phase microstructure quantitatively in a high entropy alloy of composition Co37.6 Ni35.4 Al9.9 Mo4.9 Cr5.9 Ta2.8 Ti3.5 . A very high-volume fraction of ordered L12 precipitates forms below its solvus temperature of 1156 °C that cannot be suppressed during quenching. The quench microstructure contains nanometric bimodal size distribution of spheroidal and irregular precipitates, both having L12 ordering (γ') and a Co + Ni concentration close to 75 at. %, thus representing a stoichiometry of (Ni, Co)3 (Al, Cr, Ta, Ti, Mo). The alloy shows hardening on aging with a peak in hardness value at 900 °C for 50 h of annealing. The morphology of the precipitates at this stage evolves into cuboidal shape having rounded corners with a lattice mismatch of +0.22% with the matrix. A detailed study of the coarsening behaviour of these precipitates in the matrix of complex solid solution indicates that the coarsening follows a modified LSW mechanism with estimated activation energy of 360 ± 50 kJ/mol between 900 and 1000 °C. This is slightly higher than the activation energy of most of the solutes in γ Co matrix that does not contain heavy elements like W or Re. The high-volume fraction of the precipitates together with coarsening resistance lead to an attractive high temperature strength that is higher than many of the known superalloys. Graphical abstract: Image 1